Mr. Rohinton D. Aga-An Industrialist - Aga, Rohinton D. (Journal of Engineering Education Transformations, 1995)
Mr. Rohinton D. Aga is the Chairman and Managing Director of Thermax Limited, a company actively involved in the areas of Energy and the Environment. Mr. Aga is also Chairman of Thermax Babcock & Wilcox Limited, a joint venture with Babcock & Wilcox of U.S.A., world leaders in combustion technology. The Thermax group has a turnover of around Rs. 400 crores and has a dedicated team of 3000 people.